Stem cell bioengineering and tissue engineering microenvironment - Prakash, Satya, 1962-; Shum-Tim, Dominique (World Scientific, 2011)
This is a comprehensive review of the current state of stem cell bioengineering from authorities in the field. The first part of the book includes the basic research work on stem cells and bioengineering carried out by various laboratories. The second part consists of a review of the current development of various microcapsules in stem cell therapy. The last part will summarize the overall clinical trials on stem cell therapy and myocardial regeneration as well as the most updated personal experience recently completed by well-known experts in this field.